Answer:
28
Step-by-step explanation:
f(6) = -3 * 6 + 10 = -18 + 10 = -8
g(f(6)) = g(-8)
g(-8) =
= 64 - 24 - 12 = 64 - 36 = 28
Answer: Brand B is
Explanation
(Brand A)24 diapers is 0.29¢ per diaper
(Brand B) 50 diapers is 0.27¢ per diaper
If i was a tennis player playing in wimbledon i would break that rule ;-;
The equation of a line starting from two points is:
![y-y_1=\frac{y_2-y_1}{x_2-x_1} \cdot (x-x_1)](https://tex.z-dn.net/?f=y-y_1%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D%20%5Ccdot%20%28x-x_1%29)
From the first point you get: x1 = -1, y1 = -2
From the second point you get: x2 = 3, y2 = 10
Replace x1, y1, x2, y2 in the equation of the line and you get:
![y+2=\frac{10+2}{3+1} \cdot (x+1)](https://tex.z-dn.net/?f=y%2B2%3D%5Cfrac%7B10%2B2%7D%7B3%2B1%7D%20%5Ccdot%20%28x%2B1%29)
![y+2=\frac{12}{4} \cdot (x+1)](https://tex.z-dn.net/?f=y%2B2%3D%5Cfrac%7B12%7D%7B4%7D%20%5Ccdot%20%28x%2B1%29)
![y+2=3 \cdot (x+1)](https://tex.z-dn.net/?f=y%2B2%3D3%20%5Ccdot%20%28x%2B1%29)
From this you get the equation of your line: